SIKAP POSITIF SISWA PADA PEMBELAJARAN MATEMATIKA BERBANTUAN BAHAN AJAR BERBASIS OPEN-ENDED PROBLEMS - Lucy Asri Purwasi (Jurnal Pendidikan Matematika:Judika Education, 2022)
This study aims to determine the effect of learning mathematics using teaching materials based on open-ended problems on students' positive attitudes. The research method used is the experimental method. Sample selection was done by random sampling technique. The population in this study were students of class VIII SMP Muhammadiyah Terpadu Bengkulu City. The selected sample was class VIII-A, which consisted of 28 people as the experimental class and class VIII-D, which consisted of 28 people as the control class. The results of this study indicate that the result is F = 16.06 where the value of sig <0.05 means that there is a significant interaction between students' attitude questionnaire scores (before-after) between classes (experimental-control). The interaction showed that the scores of students' attitude questionnaires between classes were significantly different. So it can be concluded that there is an effect of learning mathematics using teaching materials based on open-ended problems on students' positive attitudes. The effect of learning mathematics using teaching materials based on open-ended problems on the positive attitude of students in the experimental class is 89.8% while in the control class it is 53.8%. Keywords: positive attitude, learning mathematics, teaching materials, open-ended problems